Thermogravimetric Analysis and Chemical Kinetics for Regeneration of Sodium and Potassium Carbonate Solid Sorbents. Issue 5 (3rd May 2016) - Chaiwang, Pilaiwan; Chalermsinsuwan, Benjapon; Piumsomboon, Pornpote
Abstract : In this study, nonisothermal kinetic methods for the decomposition of potassium hydrogen carbonate (KHCO3 ) and sodium hydrogen carbonate (NaHCO3 ) were investigated by thermogravimetry (TG) and derivative thermogravimetry (DTG). Four different heating rates were measured to calculate the order of reaction ( n ), preexponential factor ( A ), and activation energy ( E a ) using four different models: Kissinger–Akahira–Sunose (KAS), Flynn–Wall–Ozawa (FWO), Kim–Park, and analytical methods. The results showed that the analytical method provided highly accurate results compared with the experimental data, whereas KAS, FWO, and Kim–Park methods gave less accurate results due to the approximation of employed equations. The order of the decomposition reaction of KHCO3 and NaHCO3 was approximately 2. The preexponential factor of KHCO3 was slightly higher than NaHCO3 . The obtained kinetic parameters from those four methods then were used to calculate the chemical reaction conversion for further applications.